The Use of AI (Artificial Intelligence) in Education - (Literature Review) - Riki Nuryadin; Marlina M (Indonesian Journal of Primary Education, 2023)
The use of artificial intelligence (AI) in education has become a topic of increasing interest in recent decades. AI has experienced rapid development and has been implemented in various aspects of education, such as adaptive learning, school administration, and increasing educational accessibility. While the potential benefits offered by AI are very promising, their implementation also faces challenges that need to be overcome. This research aims to investigate the development and use of AI in education, as well as the challenges faced in adopting and implementing it. Through a comprehensive literature review, this study evaluates the positive impact of AI in increasing learning effectiveness, providing learning experiences tailored to individual needs, and speeding up the educational administration process. However, challenges were also identified in the application of AI in education. These challenges include student data privacy issues, loss of human interaction, and the changing role of teachers in the AI era. In addition, there are also financial and infrastructural constraints that can hinder the adoption of AI in public schools. The articles cited in this research discuss various solutions that can be implemented to overcome this challenge. The conclusions in this study highlight the importance of supporting the implementation of AI in education by ensuring supportive policies, adequate preparation, and a better understanding of the use of AI by educators. In addition, it is also necessary to develop a curriculum that is adaptive and in accordance with industrial developments. By addressing these challenges, the application of AI in education has the potential to change the way we learn and teach, creating a more inclusive, efficient and quality education